Beginning XML - Hunter, David, 1974 May 7- (Wrox beginning guides., 2007)
XML is a rapidly maturing technology for the management, display and transport of data. This book offers an in-depth look at XML including what it is, how it works, what technologies surround it, and how it can be used in a variety of situations, from simple data transfer to using XML in Web pages.